Movimentos sob atração focal em campos vetoriais planares - MARTINS, Tiberio Bittencourt de Oliveira (2008)
In this work, we develop the article On the motion under focal attraction in a rotating medium , of J. Sotomayor, which deals with a bidimensional differential system that model the following Biological problem: in a shallow recipient with circular section, with liquid in, spinning with angular speed ω, there are platyhelminthes, flatworms organisms, they are attracted by a fix lighting point near of the border of the recipient and they swim with a speed v in the direction of the this point. The problem is to show that there exists an equilibrium point where platyhelminthes go to cluster by the time passing. It s analyzed the dynamic of the model: existence of critical points and stability of the system and bifurcations. We analyzed three modifications of this system too. In the last part, it s discussed a criterium for non existence of periodic orbits of a planar vector fields in a simply connected region.